Meiotic Chromosomal Abnormality Detected in a Heterozygote of Elymus nutans - Liu, Bo; Tao, Xiaoyan; Dou, Quanwen (Frontiers in Plant Science, 2022)
Elymus nutans is an allopolyploid with a genome constitution of StStYYHH (2n = 6x = 42). Highly frequent intergenomic translocations and chromosomal variations with repeat amplification and deletions in E. nutans have been identified in the previous studies. However, more complicated structural variations such as chromosomal inversions or intra-genomic translocations are still unknown in this species, so does the reason for the origin of the chromosomal variations. Heterozygotes with rearranged chromosomes always present irregular meiosis behaviors, which subsequently cause the secondary chromosome rearrangements. Investigation on the meiosis of heterozygotes, especially on the individual chromosome level, may provide the important clues to identify the more complicated chromosome structural variations in the populations, and clarify the origin of the chromosome variations. In this study, meiotic analysis was conducted on a heterozygote plant of Elymus nutans, which showed high intra- and inter-genome chromosomal variations, by sequential fluorescence in situ hybridization (FISH) and genomic in situ hybridization (GISH), with each chromosome clearly recognized. The results showed chromosomal abnormalities at every meiotic stage and abnormalities in frequency variations between different sub-genomes and different individual chromosomes. The abnormalities were revealed as univalent, fragment, rod, or Y shape bivalent in diakinesis; univalent and rod bivalent in metaphase I; lagged and segregated chromatid, bridge, fragment of the sister chromatid, fragment, bridge accompanied with fragment, and unequal segregated chromosome in anaphase I; bridge and lagged chromatid in ana-telophase II; and micronucleus at uninucleate stage. Generally, the St and H genomes harbor more abnormalities than the Y genome. Moreover, a paracentric inversion in 2St was exclusively determined, and another paracentric inversion in 6Y was tentatively identified. In addition, novel deletions were clearly detected in 3H, 4H, 1Y, and 3Y homologous chromosomes; in particular, de novo pericentric inversion in 3H was repeatedly identified in metaphase I. The study revealed the chromosomal inversions pre-existed in parents or populations, as well as de novo inversions and deletions originated in the meiosis of the heterozygote in E. nutans. Moreover, it indicated wide range of meiosis abnormalities on different stages and different chromosomes, and suggests that secondary rearrangements contribute much to the chromosome variations in E. nutans.